+0  
 
0
73
1
avatar

Assuming that x neq -5 simplify (2x + 10)^4*(x + 5)^4.

 May 4, 2023
 #1
avatar+62 
0

Lets rearrange the expression such that

(2x + 10)^4 * (x + 5)^4 = [(2(x + 5))^4 * (x + 5)^4]

Now, we can use the difference of squares identity by letting a = 2(x + 5) and b = x + 5, which gives us:

[(2(x + 5))^4 * (x + 5)^4] = [(2(x + 5))^2 * (x + 5)^2]^2 = [(4(x + 5)^2) * (x + 5)^2]^2 = [4(x + 5)^4]^2 = 16(x + 5)^8

 the simplified expression is 16(x + 5)^8.

 May 4, 2023
edited by Tacoflea  May 4, 2023

4 Online Users

avatar
avatar
avatar